Responsible Consumption and Sustainability Case Studies from Corporate Social Responsibility, Social Marketing, and Behavioral Economics - Bianchi, Enrique Carlos; Vazquez Burguete, Jose Luis.; Galan-Ladero, M. Mercedes; Lanero Carrizo, Ana. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents high-quality cases on the actions carried out by companies to minimize the social and environmental impact of the products (goods and services) they launch on the market. It also highlights the education campaigns that promote behavioral changes and new sustainable lifestyles that have been developed by all kinds of organizations (Public Administration, NGOs, and businesses), mainly from Corporate Social Responsibility, Social Marketing, and Behavioral Economics perspectives. International cases help students learn how management and corporate strategy, and the appropriate marketing strategies, can be designed with an aim to achieve responsible consumption and create sustainable lifestyles. .
0. INTRODUCTION CHAPTER -- PART I: SUSTAINABLE TOURISM & FASHION -- CASE 1. Corporate Social Marketing, Drunken Tourism, and Sustainability: The Case of Meliá Hotels International in Magaluf, Spain -- CASE 2. Green is in Fashion: Eco-Design and Circular Economy Strategies in the Fashion Industry -- CASE 3. Sustainable Business Models in Fashion Industry: An Argentine Social Enterprise Fostering an Inclusive and Regenerative Value Chain -- PART II: ENVIRONMENT -- CASE 4. Want to Be Rewarded for Recycling? With Reciclos You Can! -- CASE 5. Lesspack: A Project Helping Planet Sustainability -- CASE 6. Corporate Social Responsibility of "Ant Forest": Ant Group's "Internet + Tree Planting" Public Welfare Project -- PART III: SUSTAINABLE BUSINESS -- CASE 7. Greenbox: Ethics, Sustainable Management, and Social Commitment -- CASE 8. Corporate Social Responsibility and Sustainable Production in the Wine Industry: "Familia Torres" -- CASE 9. Providing Sustainable Solutions in Chile: Neptuno Pumps - Innovation that Flows -- PART IV: SUSTAINABLE MULTINATIONAL ENTERPRISES -- CASE 10. YPF Sustainability: Renovation of Service Stations and YPF Full Stores -- CASE 11. When Responsible Production and Consumption Matter: The Case of Danone -- CASE 12. Socially Responsible Actions For A Sustainable Life Model. The Case of the BBVA Financial Group in Mexico -- CASE 13. Sustainable Cosmetics and Perceived Brand Image on Social Networks: Comparison Between Millennial and Centennial Women -- PART V: SUSTAINABILITY IN / FROM OTHER ORGANIZATIONS -- CASE 14. Responsible Consumption and Global University Sustainability Through the UI Greenmetric World University Rankings -- CASE 15. Understanding the Evolution of Organizations Towards a Sustainable Business Model Within the Framework of the SDGs. The Case of Laboratorio de Hemoderivados- UNC -- CASE 16. Fair Trade: A Path Towards Responsible Consumption and Sustainability. The Case of Medicus Mundi.
Keywords: Industrial management -- Environmental aspects; Sustainability; Marketing; Economics -- Psychological aspects; Corporate Environmental Management; Sustainability; Marketing; Behavioral Economics